Antitermite Activity of Eucalyptus pellita Bark Extract - Andika, Riki; Arinana, Arinana; Sari, Rita Kartika; Rahmawati, Anindya Intan; Himmi, Setiawan Khoirul (Department of Forestry, Faculty of Agriculture, University of Lampung, 2025)
The study uncovers the promising anti-termite properties of Eucalyptus pellita bark extract, a resource often discarded as industrial waste in the pulp and paper manufacturing industry. It investigates the anti-termite efficacy of various extracts from E. pellita bark and identifies the extract with the highest activity, followed by a comprehensive phytochemical analysis. Samples of E. pellita inner bark, outer bark, and mixed bark were ground into 40–60 mesh powder and subjected to extraction using soxhletation techniques with successive extraction in increasingly polar solvents (n-hexane, ethyl acetate, and methanol solvents). The anti-termite activity of these extracts was evaluated using no-choice bioassays to determine the termite antifeedant activity through the weight loss percentage of test samples and the mortality rate of Coptotermes sp. Furthermore, Py-GCMS analysis was conducted on extracts exhibiting the highest anti-termite activity to elucidate their chemical composition. The findings revealed that methanol extracts from all three parts of E. pellita bark exhibited the most potent anti-termite activity against Coptotermes sp., as evidenced by the highest mortality rate (100%) and cellulose paper weight loss of 9.57 ± 6.66 mg. These methanol extracts were predominantly composed of phenolic compounds, particularly condensed tannins, suggesting a potential breakthrough in termite control. The findings indicate that E. pellita bark may be a sustainable and eco-friendly alternative to chemical pesticides for termite control. Furthermore, its utilization may facilitate waste valorization in the pulp and paper industry, thereby supporting environmental sustainability and economic efficiency. Keywords: coptotermes, decay properties, inner bark, outer bark, resistance properties